Hypoxia, Hypoxia-Inducible Factor-1α, and Innate Antileishmanial Immune Responses - Schatz, Valentin; Neubert, Patrick; Rieger, Franz; Jantsch, Jonathan (Frontiers in Immunology, 2018)
Low oxygen environments and accumulation of hypoxia inducible factors (HIF) are features of infected and inflamed tissues. Here, we summarize our current knowledge on oxygen levels found in Leishmania-infected tissues and discuss which mechanisms potentially contribute to local tissue oxygenation in leishmanial lesions. Moreover, we review the role of hypoxia and HIF-1 on innate antileishmanial immune responses.